Efficacy of a bovine colostrum and egg-based intervention in acute childhood diarrhoea in Guatemala: a randomised, double-blind, placebo-controlled trial. Issue 4 (4th December 2017) - Gaensbauer, James T; Melgar, Mario A; Calvimontes, Diva M; Lamb, Molly M; Asturias, Edwin J; Contreras-Roldan, Ingrid L; Dominguez, Samuel R; Robinson, Christine C; Berman, Stephen
Abstract : Background: Treatments for paediatric diarrhoeal disease are limited. We assessed the impact of a bovine colostrum and egg-based treatment designed to reduce diarrhoea duration through non-specific and pathogen-directed mechanisms in children. Methods: Randomised, double-blind, placebo-controlled trial of PTM202, derived from bovine colostrum and hyperimmune hen's egg on the duration of acute diarrhoeal disease in Guatemalan children. PTM202 contains specific immunoglobulins that target rotavirus, enterotoxigenic Escherichia coli, Shiga toxin-producing E. coli and Salmonella. Children aged 6–35 months presenting to three sites (one rural and two urban) with acute non-bloody diarrhoea were computer randomised to receive three daily doses of PTM202 or placebo. The primary outcome was the post-treatment duration of diarrhoea assessed in the per protocol population. Diarrhoeal pathogens were identified in stool by multiplex PCR (FilmArray Gastrointestinal-Panel, BioFire, Salt Lake City, Utah, USA). Key secondary outcomes included postdiarrhoeal weight gain and impact on diarrhoeal duration stratified by study site and presence of PTM202-targeted organisms in stool at enrolment. Safety was assessed in all participants. Results: From 9 March 2015 to 25 January 2016, 325 children were enrolled, and 301 (154 intervention and 147 placebo) were analysed for the primary outcome. No difference in diarrhoea duration was observed between intervention and placebo in the total population, but a significant reduction was observed in the treatment group among children with at least one targeted pathogen in stool (HR=1.46, P=0.02), an effect most pronounced in urban subjects (HR 2.20, P=0.007) who had fewer stool pathogens and better nutritional status. No impact on 2-week or 4-week weight gain was noted. No adverse events attributed to PTM202 occurred. Conclusion: Results demonstrate the potential to target specific pathogens occurring in children with acute non-bloody diarrhoea and shorten illness duration using a novel, safe, nutrition-based intervention. PTM202 may represent a new tool to ameliorate the effects of acute diarrhoeal disease in low/middle-income populations. Trial registration number: NCT02385773; Results.